Testing multimale mating as a strategy for improving the reproductive output of an endangered small mammal - Greggor, Alison L.; Leivers, Samantha J.; King, Shauna N. D.; Hunjan, Sumitha; Shier, Debra (Frontiers in Conservation Science, 2025)
IntroductionEffective conservation breeding requires having husbandry and breeding protocols which maximize reproductive outputs. However, often times critical information is missing about endangered species’ breeding habitats, which hampers the formation of best practice for breeding management. Females of many mammal species are suspected to mate with multiple males within a given estrous cycle, thus, we hypothesized that structuring mating opportunities for multimale mating would improve reproductive outcomes in a conservation breeding population of the critically endangered Pacific pocket mouse (Perognathus longimembris pacificus). Pocket mice possess a number of traits that suggest sperm competition is likely, and that there may be benefits to facilitating multimale mating.MethodsWe experimentally manipulated mating opportunities to determine if there where reproductive benefits to females with multimale vs single male mating.ResultsAlthough we did not find a greater likelihood of pregnancy, litter size or pup weight for multi mated females, we documented multiple paternity and a first mating advantage which suggest multimale mating may have benefits in specific cases.DiscussionIn determining that only a narrow application of multimale mating would benefit Pacific pocket mice, we explore how using an experimental framework to test different mating strategies can prevent wasting resources and increase the efficiency of breeding programs.